Switching to nonacog beta pegol in hemophilia B: Outcomes from a Canadian real‐world, multicenter, retrospective study. Issue 3 (31st March 2022) - Matino, Davide; Iorio, Alfonso; Keepanasseril, Arun; Germini, Federico; Caillaud, Alexandre; Carcao, Manuel; Hews‐Girard, Julia; Iserman, Emma; James, Paula; Lee, Adrienne; Phua, Chai W.; Sun, Haowei (Linda); et al.
Abstract: Background: The Canadian Bleeding Disorders Registry (CBDR) captures data from 24 hemophilia treatment centers and patients directly. Nonacog beta pegol (N9‐GP) was approved in Canada in 2018. Objectives: To assess treatment outcomes following switching to N9‐GP in a real‐world setting. Methods: CBDR data for Canadian male patients (aged 7–72 years) with hemophilia B receiving prophylactic N9‐GP for ≥6 months as of March 31, 2021, were included. To allow comparison with the previously used products, only patients for whom data were available in the CBDR for at least 6 months before the switch to N9‐GP were included in this retrospective analysis. Results: Forty‐two patients were included in the analysis (total observation period: 148.0 patient‐years). The distribution of disease severity was 62% severe, 36% moderate, 2% mild, with 62% of patients previously receiving recombinant factor IX‐Fc‐fusion protein (rFIXFc) and 38% previously receiving standard half‐life (SHL) recombinant factor IX (rFIX). During a median follow‐up period of 2.3 years on N9‐GP prophylaxis, 232 bleeds were reported in 30 patients, 29% of patients reported zero bleeds. The median overall annualized bleeding rate on N9‐GP was 0.73 for patients switching from rFIXFc (previously 1.44) and 2.10 for patients switching from SHL rFIX (previously 6.06). Median total annualized factor consumption (IU/kg) was lower with N9‐GP than with previous SHL rFIX (2152 vs 3018) and previous rFIXFc (1766 vs 2278). Conclusions: Results from this first real‐world study of N9‐GP in patients with hemophilia B suggest optimal bleeding control with low factor consumption after switching to N9‐GP, irrespective of the previous product. Abstract :